Decolourization of Azo Dye Direct Blue 15 Using Batch Culture of Klebsiella sp - Chong, Chun Siong; Ibrahim, Zaharah; Md Salleh, Madihah; Abdulrashid, Noor Aini; Yahya, Adibah; Wui, Jin Wong (School of Postgraduate Studies, UTM, 2006)
Nowadays, the development of textile industries are mushrooming and the pollution resulting from the dye-wastewater is alarming. Colour is recognized as the first contaminant from the dye containing wastewater. The present study reports the decolourization of Direct Blue 15 by Klebsiella sp., originated from textile wastewater plant. The important parameters, including co-substrates, aeration, starting pH of culture and temperature for decolourization, were investigated. Mechanism of colour removal either by bioadsorption or biodegradation was determined. Amongst the co-substrates, glucose (0.2% w/v) was the preferred co-substrate for decolourization of Direct Blue 15. The optimal decolourization occurred under partial anaerobic condition at starting pH of about 6.0. Decolourization of Direct Blue 15 was most efficient at 45oC. Under the optimum conditions, it was found that the COD removal was 53.6%. Dye decolourization (81.9%) was successfully achieved within 24 hours; 0.03% was due to the bioadsorption and 81.87% was due to the biodegradation by Klebsiella sp., while the product of degradation of azo dye, sulfanilic acid, was detected using HPLC.